2020
DOI: 10.3390/bs10100148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Worry-Induced Sleep Disturbance and Associated Factors among a National Sample of In-School Adolescents in Lebanon

Abstract: Persistent worry can cause significant distress among adolescents. The goal of this study was to estimate the prevalence and correlates of worry-induced sleep disturbance (WISD) among adolescent school children in Lebanon. Cross-sectional, nationally representative data were analysed from 5849 adolescents (15 years median age) that took part in the “2017 Lebanon Global School-Based Student Health Survey (GSHS)”. The results indicate that the prevalence of WISD was 14.7%, 9.6% among males and 17.2% among female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(49 reference statements)
2
3
0
Order By: Relevance
“…The association between being sedentary and psychological distress may also be explained by the inflammatory process . The result also showed that drug use was associated with anxiety-induced sleep disturbance, which is congruent with findings from past studies (Ahinkorah et al, 2021;Pengpid & Peltzer, 2020b). The use of drugs as a coping attempt for stress among adolescents might be dysfunctional and maladaptive that can trigger anxiety disorders (Ahinkorah et al, 2021;Buckner et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The association between being sedentary and psychological distress may also be explained by the inflammatory process . The result also showed that drug use was associated with anxiety-induced sleep disturbance, which is congruent with findings from past studies (Ahinkorah et al, 2021;Pengpid & Peltzer, 2020b). The use of drugs as a coping attempt for stress among adolescents might be dysfunctional and maladaptive that can trigger anxiety disorders (Ahinkorah et al, 2021;Buckner et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Understanding factors associated with adolescent psychological distress is important since the onset of major mental health conditions usually occurs during adolescence and the detrimental consequences of untreated adolescent mental health problems might persist and extend to adulthood (Kessler, Amminger, et al, 2007;World Health Organization, 2020). Age (Pengpid & Peltzer, 2020a), gender (Siziya & Mazaba, 2015), health-related behaviours, such as substance use (cigarette smoking, alcohol use, or drug use) (Ahinkorah et al, 2021;Pengpid & Peltzer, 2020b) and sedentary behaviour (Vancampfort, Ashdown-Franks, et al, 2019; were found to be associated with psychological distress among adolescents. In addition, according to a conceptual framework proposed by World Health Organization (2005), adolescents' social environments, including parental-, school-or friend-, and communityinduced factors can serve as either a risk or protective factor for their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…A marked sex difference was found in this cross-sectional study with respect to the prevalence of anxiety-related sleep disturbances, which was more than twice as high in girls as in boys. This finding agrees with previous studies that found that anxiety-related sleep disturbances are more prevalent among girls ( Pengpid and Peltzer, 2020 , 2022 ; Werneck et al, 2020 ). Regarding the causes of inadequate sleep in adolescents, internal biological processes have been identified, such as the normal change (delay) in circadian rhythm that occurs in relation to puberty and a development-based slowing of the “sleep drive” ( Owens and Weiss, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Of note, FI is often used as an indicator of individuals' low socioeconomic status and insufficient nutrient intake (4,9,27). Indeed, using nationally representative cross-sectional data from GSHS, FI was found to be associated with sleep disturbance in Benin and Lebanon adolescents (28,29). Compared with the evidence from adolescents (30)(31)(32)(33)(34), there are relatively more studies on the relationship between FI and sleep disturbance in adults.…”
Section: Introductionmentioning
confidence: 99%